1994
DOI: 10.1093/ajcp/101.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Major Diagnoses in a Binational Study of Lung Cancer in Uranium Miners and Atomic Bomb Survivors

Abstract: A binational panel of four Japanese and four American pathologists examined 208 pulmonary neoplasms, according to the World Health Organization (WHO) recommendations, second edition, for the histologic typing of lung tumors. The study design included independent evaluations by pathologists working alone, followed by group reviews. The individual evaluations, and their implications for reproducibility of the WHO recommendations, are reported. Consensus (agreement by six or more pathologists) with respect to maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In both studies the discrepancies found were important, as they altered the treatment given. A diagnostic concordance rate of 94% is higher than that for tumours of the breast (92% for the presence of invasive carcinoma, with poor agreement on histological type [ 3]) and lung (72% for small cell carcinoma [ 4]). In seven biopsies the initial report used confusing terminology; it is essential that standard terminology is used in the pathology report.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies the discrepancies found were important, as they altered the treatment given. A diagnostic concordance rate of 94% is higher than that for tumours of the breast (92% for the presence of invasive carcinoma, with poor agreement on histological type [ 3]) and lung (72% for small cell carcinoma [ 4]). In seven biopsies the initial report used confusing terminology; it is essential that standard terminology is used in the pathology report.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is one that is poorly understood by many outside of pathology who fail to appreciate the limitations of tumour classification on small biopsy specimens or the necessity for using such terms as ‘non‐small cell’ carcinoma. It is clear that even when very experienced pulmonary pathologists spend time examining small biopsy specimens against agreed criteria for squamous or glandular differentiation, there will be insufficient features present to classify these accurately in around 50% of cases 2–5 . It must also be appreciated that even when specific features of glandular or squamous differentiation are identified in small biopsy specimens, the frequency of variable differentiation in lung carcinomas means that a subsequent resection, if performed, may be classified differently 2,5 .…”
Section: Can We Improve Classification Of Poorly Differentiated Tumours?mentioning
confidence: 99%
“…It is clear that even when very experienced pulmonary pathologists spend time examining small biopsy specimens against agreed criteria for squamous or glandular differentiation, there will be insufficient features present to classify these accurately in around 50% of cases. [2][3][4][5] It must also be appreciated that even when specific features of glandular or squamous differentiation are identified in small biopsy specimens, the frequency of variable differentiation in lung carcinomas means that a subsequent resection, if performed, may be classified differently. 2,5 Equally, pathologists need to be aware of the increasing requirements of oncologists in relation to future potential treatment options for tumour subtypes and be prepared to adapt their practice accordingly.…”
Section: Pulmonary Blastomamentioning
confidence: 99%
See 2 more Smart Citations